Modern methods of design and analysis of optical systems on example of the off-axis catadioptric system - Nurguzhin, M.; Kaliyev, A.; Zhumazhanov, B. Zhumazhanov (Recent Contributions to Physics, 2014)
The article is devoted to the technology of mechanical design and analysis of the 3D model of the optical payload. Optical payload (OPN) is used for the remote sensing (RS) on small satellites. A brief description of the software used for the design of optical systems and some of its features are presented. The basic stages of the design of mechanical parts of the optical payload are described on the example of a catadioptric system. Some of the factors considered at designing and results of the static analyses of the optical system are presented, after which it is possible to provide a preliminary 3D model of the system. The article is based on the work done by the specialists of the JSC «National company «Kazakhstan Gharysh Sapary» in frames of the project «Creation of the remote sensing space system of the Republic of Kazakhstan». The works are done in collaboration with the specialists of companies EADS Astrium (France) and SSTL (Great Britain). The article presents the general view of modern methods of developing optical payloads for small satellites.